Perilaku Masyarakat Pesisir Tentang Pencegahan Penyebaran Corona Virus Disease 2019 - Oksfriani Jufri Sumampouw; Van Grayen Lowing; Odi Roni Pinontoan (Universitas Sam Ratulangi, 2021)
Background: The Corona virus is a group of viruses that can cause disease in animals and humans known as Corona Virus Desease 2019 (Covid-19). In humans, this virus can cause respiratory infections ranging from mild flu, coughs, colds to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The purpose of this study was to describe the behavior of coastal community about prevention of the spread of Covid-19. Method: This is a descriptive study which was conducted in Desa Atep Oki Kecamatan Lembean Timur in August-December 2020 with 80 respondents. The variables in this study were knowledge, attitude, and action. The instruments used were questionnaires, cameras, and writing instruments. Data analysis was carried out by univariate. Results: The results of this study showed that the coastal community in the Atep Oki Village are mostly in the 61.3% of respondents have a good level of knowledge, 57.5% of respondents have a good attitude and 65.0% of respondents have good actions. Conclusion: This is can concluded the coastal communities in Atep Oki Village have good knowledge, attitudes, and actions in preventing the spread of Covid-19. Therefore, it is necessary to maintain and improve people's behavior through health promotion efforts.